PV Supplied Single Stage MPPT Inverter for Induction Motor Actuated Ventilation Systems - Ozdemir, S.; Altin, N.; Sefa, I.; Bal, G. (Elektronika ir Elektrotechnika, 2014)
Ventilation and refrigeration is indispensable process for human life. Particularly, it has vital importance in desert climate conditions and rural areas, where the grid power may not be available. Although the cost is still higher than traditional energy resources, renewable energy may be the right choice for these applications. In this paper, a DSP based variable speed drive for induction motors to actuate a ventilation system supplied photovoltaic arrays is proposed. The maximum power point of the photovoltaic arrays is tracked by proposed variable speed drive. A variable stepped incremental conductance and constant voltage methods are combined to obtain fast tracking algorithm which generates voltage and frequency references for three phase three level inverter. Also the switching frequency of the inverter is kept constant to improve the quality of current waveform at low power levels. Experimental results show that, the proposed system has fast reaction and is suitable for rapidly changing irradiation level. Since the additional converter requirement is eliminated by using single stage inverter, the total system efficiency is increased. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7111